Polish Organizations and Chicago's Polonia, 1880-1930 - (:unkn) unknown (My University, 2020)
Despite a large, growing amount of literature on the Polish community in Chicago, there remains a lack of information about organizations in the Polish communities. Organizations in the Polish community are generally spoken about in one of two ways. Either one organization is spoken about in great depth or organizations are barely touched upon. This work seeks to bridge both of those types of work by focusing both on small organizations and large organizations and connecting them through the Poles who were members. The Oral History of Chicago’s Polonia project, 1880-1930, is used in this work to limit the number of organizations that are discussed and to focus on how Polish immigrants were affected by multiple organizations. How organizations helped shape and were shaped by Chicago’s Polish community is a focal point of this work. This work explores how the shifting of Polish identity affected how organizations were developed and how they changed. It finds that Polish tradition and Polish Americanization played a role in organizations’ development, which in turn influenced the development of Polonia.
Keywords: Chicago; immigrants; Organizations; Polish; Polish Americans; Polonia